Durvalumab-Induced Demyelinating Lesions in a Patient With Extensive-Stage Small-Cell Lung Cancer: A Case Report - Liu, Wenhui; Chen, Bo; Liu, Yiping; Luo, Zhiying; Sun, Bao; Ma, Fang (Frontiers in Pharmacology, 2022)
It is of great clinical value to investigate the immune-related adverse events (irAEs), especially demyelinating lesions, caused by immune checkpoint inhibitors (ICIs). The incidence of demyelinating lesions is less frequent in irAEs, but once it occurs, it will seriously affect the survival of patients. The present study reports a case of durvalumab-induced demyelinating lesions in a patient with extensive-stage small-cell lung cancer. Subsequently, the patient receives a high intravenous dose of methylprednisolone and his condition is improved after 21 days of treatment. Altogether, early diagnosis and treatment of ICIs-related neurological irAEs is of great significance to the outcome of the patient's condition.